Research on the Deformation Mechanism of Mining Roadway Stratiform Surrounding Rock with Nonuniform Stress Field - Yongxin Sun (Shock and Vibration)
Aiming at the failure problems of mining roadway stratiform surrounding rock influenced by asymmetrical high stress, firstly, the rock instability conditions of different structural plane angles were summarized based on the mechanical model of rock joints and instability criterion. Secondly, stresses, plastic zone, and displacement of surrounding rock with different structural plane angles were calculated and analyzed with the theoretical calculation method or numerical simulation method, respectively. The distribution characteristics of plastic zone of surrounding rock under different influence factors are further studied, and the results show that the lateral pressure coefficient can change the size and shape of plastic zone at the same time. The damage mechanism was analyzed through the above study. Research studies show that the shear and tension failure area of plastic zone were directly determined by the maximum shear stress and the minimum principal stress. The effect of structure planes on stress has two sides, one to destroy the continuity and the other to strengthen discreteness and laddering nature. When the angle between maximum shear stress and structure plane increases, the extended mode and distribution pattern of plastic zone change substantially as well. The #15 haulage roadway is taken as engineering background, and the above research’s results are verified by the comprehensive analysis. The research results can enrich the butterfly plastic zone theory and provide the basis for roadway supporting design.